Karakteristik Antrian Kapal Dan Faktor-Faktor Yang Mempengaruhi Waktu Tunggu Kapal (Waiting Time) Di Pelabuhan Tanjung Perak - Frizky Andrian Perdana; Alwafi Pujiraharjo; Indradi Wijatmiko (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Economic growth in Indonesia especially in East Java and Eastern Indonesia has caused the number of ship visits in Tanjung Perak Port to increase. These conditions resulted in a higher ship queue that will linearly cause the waiting time of the ship (waiting time) in the port which is getting longer. Therefore it is necessary to study about the average of ship waiting time, the characteristics of ship queue, the factors that affect the waiting time of the ship, the direction of improvement. This study uses the Queue Analysis Method, Multiple Regression Analysis and SWOT Analysis. The analysis shows that the average waiting time at Tanjung Perak Harbor is the longest in the northern and western emerald terminal of 46.20 hours, and the smallest is in the diamond terminal 29.94 hours and the terminal of 29 , 94 hours. From queuing characteristics, the percentage of server usage of northern and western emerald terminal terminal has exceeded the capacity of 124.44%, while the southern emerald terminal is 94.40%, Diamond Terminal is 70.56%, Multipurpose Terminal is 84.31%, and Mirah terminal 85.24%, From the simulation of North and West Jamrud Terminal requires at least 7 servers. The most influential factor on (waiting time) is the Availability of Pier (X4) of 13.25% and then the effect of the Production of Loading and Unloading (X1) of 12.11% with the regression model obtained is Y = 403.914-8.198 X1-6.551X2- 4,874 X3-6,409 X4-6,909 X5. The Strategy must be done to decrease the waiting time of ships at Tanjung Perak Port by maximizing the performance of the loading and unloading force (TKBM), transferring the vessel to dock at the surrounding ports such as Lamong Bay Terminal and Manyar BMS Gresik Terminal and improving services and document processing procedures at the port to cope with the increase in the flow of goods. Developing Surabaya's West Sailing Channel (APBS) to revitalize the Sailing Flow and harbor pools, implement correct port regulation and maximize existing guidance to anticipate the increase in ship visits.